In-hospital Mortality Rates in SARS-CoV-2 Patients Treated with Enoxaparin and Heparin. (October 2022) - Alroomi, Moudhi; Alsaber, Ahmad; Al-Bader, Bader; Almutairi, Farah; Malhas, Haya; Pan, Jiazhu; Zhanna, Kobalava D.; Ramadhan, Maryam; Saleh, Mohammad Al; Abdullah, Mohammed; Alotaibi, Naser; AlNasrallah, Noor; et al.
Аbstrасt: Objectives: This study aimed to investigate in-hospital mortality rates in patients with coronavirus disease (COVID-19) according to enoxaparin and heparin use. Methods: This retrospective cohort study included 962 patients admitted to two hospitals in Kuwait with a confirmed diagnosis of COVID-19. Cumulative all-cause mortality rate was the primary outcome. Results: A total of 302 patients (males, 196 [64.9%]; mean age, 57.2 ± 14.6 years; mean body mass index, 29.8 ± 6.5 kg/m 2 ) received anticoagulation therapy. Patients receiving anticoagulation treatment tended to have pneumonia (n = 275 [91.1%]) or acute respiratory distress syndrome (n = 106 [35.1%]), and high D-dimer levels (median [interquartile range]: 608 [523;707] ng/mL). The mortality rate in this group was high (n = 63 [20.9%]). Multivariable logistic regression, the Cox proportional hazards, and Kaplan-Meier models revealed that the use of therapeutic anticoagulation agents affected the risk of all-cause cumulative mortality. Conclusion: Age, hypertension, pneumonia, therapeutic anticoagulation, and methylprednisolone use were found to be strong predictors of in-hospital mortality. In elderly hypertensive COVID-19 patients on therapeutic anticoagulation were found to have 2.3 times higher risk of in-hospital mortality. All cause in-hospital mortality rate in the therapeutic anticoagulation group was up to 21%.